Bibliometric analysis of multimodal analgesia research in the perioperative period: trends, contributions, and emerging areas (2013–2023) - Jiang, Wenchen; Qin, Yi; Chen, Liang (Frontiers in Medicine, 2025)
ObjectivesMultimodal analgesia (MA) is a cornerstone in perioperative pain management, enhancing pain relief and minimizing opioid consumption by targeting various pain pathways. This study conducts a bibliometric analysis of MA research from 2013 to 2023 to understand its development and impact on perioperative care.MethodsA comprehensive literature search of the Web of Science Core Collection (WOSCC) was conducted, covering publications from January 2013 to December 2023. Data were analyzed using VOSviewer and other bibliometric tools to identify publication trends, key contributors, and emerging research themes.ResultsThe analysis identified 1,939 studies on MA, with a notable increase in annual publications since 2020. The USA, China, and Canada were the leading contributors. Key terms like Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), Enhanced Recovery After Surgery (ERAS), and Patient-Controlled Analgesia (PCA) were frequently associated with MA. Significant journals included the Cureus Journal of Medical Science and Anesthesia and Analgesia. Influential authors such as Richard D. Urman and Henrik Kehlet were highlighted for their contributions. The research showed significant advancements and growing global interest in MA.ConclusionThe study underscores the growing importance of MA in perioperative pain management, with significant contributions from leading countries and researchers. Future research should focus on optimizing pain management protocols, enhancing patient recovery, and reducing opioid dependency through MA.